ABERRATIONS MINIMIZATION FOR IMPROVING CHARACTERISTICS OF COMPACT HIGH-APERTURE DISPERSIVE SPECTROMETERS - E. S. Voropay; I. M. Gulis; A. G. Kupreev; A. G. Kostiukevich (Приборы и методы измерений)
Schemes of high-aperture and compact optical spectrometers and giperspectrometer with minimized aberrations are presented. In the first scheme usage of inclined plane-parallel plate allows decreasing of astigmatism. In the second scheme off-axis aberrations are practically removed due to axial propagation of light. For giperspectrometer narrowing of light propagation angle through the object lens and turning the light out of dispersion plane lead to minimizing of picture aberrations.